PENGEMBANGAN POTENSI WIRAUSAHA DI DESA MEKARGALIH, KECAMATAN JATINANGOR, KABUPATEN SUMEDANG - Rudi Saprudin Darwis; Sri Sulastri; Maulana Irfan (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Micro, small, and medium enterprises (MSMEs) in the Mekargalih Village area, Jatinangor District, Sumedang Regency still face problems of weak business capacity, uncertain market access and development, ineffective business management, and limited business networks. This paper will describe efforts to develop the capacity of SMEs in Mekargalih Village through workshops on entrepreneurship. The studio filled with material delivery on developing entrepreneurial insight, promoting product legality through halal certification and brand rights, as well as sharing experiences from MSME actors in the Mekargalih Village. In the implementation, not all invited participants could attend because the implementation time was in conjunction with other community activities. The results of the evaluation of participants who attended, using the Wilcoxon Test method, showed the workshop influenced increasing the knowledge of participants even though the increase was small. For the aspects of 'business development according to the target market,' there was no increase in knowledge. As a suggestion, providing material for business development following the target market needs to be accompanied by the presentation of real data to be the basis for business development.